Identification of HLA-B27-restricted peptides from the Chlamydia trachomatis proteome with possible relevance to HLA-B27-associated diseases. - Kuon, W; Holzhütter, H; Appel, H; Grolms, M; Kollnberger, S; Traeder, A; Henklein, P; Weiss, E; Thiel, A; Lauster, R; Bowness, P; Radbruch, A; et al. (2001)
The association of HLA-B27 with ankylosing spondylitis and reactive arthritis is the strongest one known between an MHC class I Ag and a disease. We have searched the proteome of the bacterium Chlamydia trachomatis for HLA-B27 binding peptides that are stimulatory for CD8(+) cells both in a model of HLA-B27 transgenic mice and in patients. This was done by combining two biomathematical computer programs, the first of which predicts HLA-B27 peptide binding epitopes, and the second the probability of HLA-B27 peptide generation by the proteasome system. After preselection, immunodominant peptides were identified by Ag-specific flow cytometry. Using this approach we have identified for the first time nine peptides derived from different C. trachomatis proteins that are stimulatory for CD8(+) T cells. Eight of these nine murine-derived peptides were recognized by cytotoxic T cells. The same strategy was used to identify B27-restricted chlamydial peptides in three patients with reactive arthritis. Eleven peptides were found to be stimulatory for patient-derived CD8(+) T cells, of which eight overlapped those found in mice. Additionally, we applied the tetramer technology, showing that a B27/chlamydial peptide containing one of the chlamydial peptides stained CD8(+) T cells in patients with Chlamydia-induced arthritis. This comprehensive approach offers the possibility of clarifying the pathogenesis of B27-associated diseases.